Comparative Evaluation of Effectiveness of Intravenous Paracetamol and Intravenous Diclofenac as Post-operative Analgesia in Laparoscopic Cholecystectomy - Kharbuja, Kalpana; Sharma, Mahesh; Sharma, Nil Raj (Journal of Lumbini Medical College, 2018)
Introduction: Though the development of minimally invasive surgery has revolutionized the field of surgery, post-operative pain is still a significant issue. Unlike in the past, concerns about adverse effects have limited the role of opioids in post-operative pain management. This study aims to compare the effectiveness of intravenous paracetamol and diclofenac as postoperative analgesia in laparoscopic cholecystectomy. Methods: One hundred and twenty eight patients of American Society of Anesthesiologists (ASA) categories I and II included in this study were divided into two groups. Anesthesia induction and maintenance were standardized. The first group received 15mg/kg (maximum 1gm) intravenous paracetamol and the second group received 2mg/kg (maximum 75mg) intravenous diclofenac 30 minutes prior to ending of surgery. A questionnaire was responded by patients and chart was maintained by visual analogue scale. Mann Whitney U test was used to analyze quantitative data and Chi-square test for categorical data. P value <0.05 was considered statistically significant. Results: Profiles of hemodynamic changes were almost similar in both groups with respect to heart rate and blood pressure. However, paracetamol infusion provided hemodynamic stability in post-operative period. We observed statistically significant differences in visual analogue scale between the two groups. Most of the patients in paracetamol group had low mean pain scores in post-operative period and provided an extended analgesia compared to diclofenac. No serious postoperative complication was observed in paracetamol group. Conclusion: Administration of intravenous paracetamol has better and prolonged analgesic effect with low mean pain score and less requirement for rescue analgesia compared to diclofenac. DOI: https://doi.org/10.22502/jlmc.v6i2.248